2020
DOI: 10.2196/19803
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Web-Based Mindfulness With Loving-Kindness and Compassion Training for Promoting Well-Being in Pregnancy: Protocol for a Three-Arm Pilot Randomized Controlled Trial

Abstract: Background Promoting psychological well-being and preventing distress among pregnant women is an important public health goal. In addition to adversely impacting the mother’s health and well-being, psychological distress in pregnancy increases the risk of poor pregnancy outcomes, compromises infant socioemotional development and bonding, and heightens maternal and child vulnerability in the postpartum period. Mindfulness and compassion-based interventions show potential for prevention and early int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“… 41 A pilot RCT (Mums Minds Matter) investigated the feasibility and engagement in a randomized controlled trial protocol comparing three meditation-based interventions delivered on the Internet during pregnancy. 62 In addition, the Mums Minds Matter study explored barriers and enablers to online well-being training, along with engagement in other types of well-being practices. 63 Our analysis of Mums Minds Matter, along with this current study will be used to design an appropriately tailored mobile app for a future full-scale randomised controlled trial (RCT) comparing mental health outcome in perinatal women who undertake an online mindfulness, loving kindness, or general relaxation programme.…”
Section: Discussionmentioning
confidence: 99%
“… 41 A pilot RCT (Mums Minds Matter) investigated the feasibility and engagement in a randomized controlled trial protocol comparing three meditation-based interventions delivered on the Internet during pregnancy. 62 In addition, the Mums Minds Matter study explored barriers and enablers to online well-being training, along with engagement in other types of well-being practices. 63 Our analysis of Mums Minds Matter, along with this current study will be used to design an appropriately tailored mobile app for a future full-scale randomised controlled trial (RCT) comparing mental health outcome in perinatal women who undertake an online mindfulness, loving kindness, or general relaxation programme.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, web-based, minimal contact interventions could provide ready access to the resources needed during crisis periods. A current study is investigating the feasibility of a randomised controlled trial protocol comparing three meditation-based interventions delivered on the web during pregnancy [ 38 ]. If the study is shown to be feasible, results will be used to inform a future full-scale RCT in order to develop evidence-based, scalable, and low-cost interventions that promote wellbeing and reduce psychological distress among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The training programs were available via the Teachable website and are minimal interventions with no direct interaction with a therapist or other users. The full study protocol includes detailed information on the battery assessment questionnaires administered before, during, and after the intervention, as well as the intervention format and structures [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…A range of measures were collected in the full pilot RCT, as outlined in the protocol [ 4 ], but not analyzed and reported in this paper. Midway through the intervention, the project team assessed survey completion rates, and, owing to low compliance and perceived participant burden, the regular engagement survey collection frequencies were reduced from weekly to fortnightly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation